The study of steroidal compounds in canna plant material - Tymofieieva, Svitlana; Kyslychenko, Oleksandra; Zhuravel, Iryna (ScienceRise: Pharmaceutical Science, 2017)
Aim. Identification and quantitative determination of steroidal compounds in Canna roots, rhizomes, leaves and flowers. Methods. Identification and quantitative determination of steroidal compounds in Canna herbal material was carried out by Gas chromatography – Mass spectrometry method (GC/MS). Results. In result of the study, 15 steroidal compounds were identified in Canna roots, 11 compounds – in rhizomes, 12 – in leaves, and 3 – in flowers. β-sitosterol, campesterol, and stigmasterol dominated quantitavely in all studied samples. The content of steroidal compounds in Canna was: 138.6 mg/kg in leaves, 130.5 mg/kg in roots, 126.7 mg/kg in rhizomes, and 37.01 mg/kg in flowers. During the research work it was found that β-sitosterol was dominating compound by its quantitative content in all types of Canna plant material. Its content was 60.2 mg/kg in rhizomes, 57.0 mg/kg in roots, 47.0 mg/kg in leaves, and 31.52 mg/kg in flowers. Conclusion. The obtained results can be used for development of the methods for Canna quality control, as well as for obtaining biologically active substances from the herbal material